2006
DOI: 10.3892/or.16.4.871
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic activity of high-dose intravenous calcitonin in cancer patients with bone metastases

Abstract: Abstract. We undertook a prospective, nonrandomized study with the objective to evaluate the efficacy of salmon calcitonin (sCT) in controlling pain secondary to bone metastases. Our study population consisted of 45 cancer patients with bone metastases (26 men) with a mean age of 64 years (range, 48-70) who had completed chemotherapy, hormonal therapy and radiation therapy at least 30 days prior to enrollment in the study, and had intractable pain despite the use of common analgesics (acetaminophen, nonsteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Intravenous salmon calcitonin (sCT) has been trialed in efforts to achieve analgesia from painful ossewww.painphysicianjournal.com ous metastases. Although there exist anecdotal reports of minor benefit (146,147), a larger prospective study demonstrated that intravenous calcitonin administered in a relatively high dose has a very limited therapeutic potential as an adjuvant analgesic in cancer patients with bone metastases (148). In 2003, Martinez and colleagues (149) performed a Cochrane Review and found that the limited evidence currently available for systematic review does not support the use of calcitonin to control pain from bone metastases.…”
Section: Calcitoninmentioning
confidence: 99%
“…Intravenous salmon calcitonin (sCT) has been trialed in efforts to achieve analgesia from painful ossewww.painphysicianjournal.com ous metastases. Although there exist anecdotal reports of minor benefit (146,147), a larger prospective study demonstrated that intravenous calcitonin administered in a relatively high dose has a very limited therapeutic potential as an adjuvant analgesic in cancer patients with bone metastases (148). In 2003, Martinez and colleagues (149) performed a Cochrane Review and found that the limited evidence currently available for systematic review does not support the use of calcitonin to control pain from bone metastases.…”
Section: Calcitoninmentioning
confidence: 99%
“…Calcitonin is a rapid-acting peptide hormone secreted by the parafollicular C cells of the thyroid gland, which is a useful adjunctive initial therapy that inhibits osteoclastic bone resorption and renal calcium reabsorption [15,64]. It is approved by Food and Drug administration (FDA) and when used with bisphosphonates, it can lower calcium level more rapidly than either agent alone.…”
Section: Duration Of Actionmentioning
confidence: 99%